Educational Literacy Based on Local Wisdom to Equip the National Character of Indonesian Migrant Workers - Khoiri, Ahmad; Sukawi, Z; Irianto, H; Affandi, A; Aprilia, RL; Maemunah, T; Hermawan, R; Priyanto, E; Sejati, H; Handriani, E; Legowo, YAS; Sutomo, S; Hafni, ND (Carmin: Journal of Community Service, 2024)
Educational literacy based on local wisdom still needs to be improved among the children of Indonesian Migrant Workers (PMI) in Malaysia, specifically at the Sungai Mulia 05 Gombak Kuala Lumpur Learning Studio. Literacy is focused on strengthening national character and belonging to a sense of nationalism in one's country of origin. Based on this background, it is necessary to carry out international community service which is facilitated through the NU (Nahdlatul Ulama) higher education community in Indonesia. Implementation of the service takes 4 months (August-November 2024). Pre-implementation stages of coordination, MoU and MoA for 2 months, activity orientation (1 month) followed by introduction to Indonesian Local Wisdom Education, questions and answers and reflection or follow up on activities (1 month). The method of implementing service is through lectures, demonstrations and direct questions and answers with activity participants. The results obtained increased participants' understanding of local wisdom-based education literacy in Indonesia with the aim of paying attention to learning motivation and being able to strengthen the national character of the country of origin of Indonesia. The participants' responses were very varied, including only a small number of participants who knew iconic areas in Indonesia. The achievement of international service activities was 76.4% very good response. The benchmark for the success of this activity is to familiarize students with carrying out teaching and learning activities more focused and maximally. Applying appropriate learning methods can increase students' interest and enthusiasm for learning. As a follow-up to the activity, the learning studio participants have the enthusiasm to continue their education to junior high school level in Indonesia and strengthen their national character as the successor to the golden generation of 2045. Because the available learning studios are not like formal educational institutions in general, so they must be one of the considerations in evaluation and follow-up regarding the quality of education provision.